High Temperature Processing of Fish Sausage III - Studies on Some of the Storage Characteristics - VICTOR RAJ, M. CROSS; CHANDRASEKHAR, T. C. (Fishery Technology, 2017)
The proximate compos1t1on of the high temperature processed fish sausagewas found to be 14.56 % protein, 4.65 % fat, 69.14 % moisture, 2.12 % ::i.sh and 8.12 % carbohydrate. The quality of the product during storage was assessedon the basis of the changes observed in the physical, chemical and microbiologicalparameters. The results of the different tests such as pH, volatile base nitrogen(VBN), trimethyl amine nitrogen (TMA-N) and jelly strength are summarisedand discussed. The total bacterial load increased gradually during storage butwas not proportional to the initial load.